Eksistensi CV. Andromeda Utama untuk Menghadapi Persaingan Usaha dalam Perspektif Manajemen Pemasaran Syari’ah - Hayatul Millah (Fakultas Ekonomi dan Bisnis Islam, 2017)
In the world of self-employment, competition is a matter of course. Competition is the color of the self-employed. In the absence of competition, the bekerjapun tasted bland. Competition is also a motivation to promote the business and make the bakerja more spirit to confront obstacles. Competition may have an adverse impact also on our businesses, when a the employer is unable to control himself in the face of competition so that employers compete with imperfect or unhealthy. It is also fatal to a company. Existence CV. Top Andromeda in the face of competition, especially in the field of travel deserves more attention, this is because the CV. Top Andromeda relatively new company and an individual effort when compared to other tourism services company much longer cultivate this field and is a venture managed by a few people who are experienced and more expert in this field. The functions of marketing management CV. Andromeda MAIN order to face the competition in the marketing management perspective of Shariah is the function of marketing management is the spearhead of a company in profit and ability to survive in the competitive workplace. Andromeda CV Utama Tours, Travel and Ticketing has setrategi marketing as contained in its strategic plan, namely Marketing Strategy mixture